CREATOR CONTENT CAPACITY INCREASE AT MADRASAH ALIYAH BY MADANI WEST BANDUNG REGENCY - Candra, Muhammad Fazri; Muttaqien, Muhammad Ersyad; Angela; Kautsar, Malida Firyal (Pasundan International of Community Services Journal (PICS-J), 2023)
In the development of the current digital era, content plays a very important role that is supported by internet technology so that the process of spreading information is faster. Internet technology brings significant changes to learning patterns that help the communication process between students and the school more interactively. The high dependence of society on the use of the internet is able to open up new opportunities to pursue various professions, one of which is becoming a content creator. Based on the phenomenon above, the community service team takes a role in providing guidance and assistance to the students of Madrasah Aliyah Karya Madani regarding the improvement of content creator capacity due to lack of knowledge and advantages about the internet so that they can be used with the content creator profession, get positive things to be a content creator, and lack of ability to create content.